Feeling the fit and self-determination? A PLS-SEM approach for self-initiated expatriates' self-determination, person-environment fit and turnover intention. (23rd January 2023) - Chou, Shih Yung; Chang, Tree; Han, Bo
The purpose of this study is to investigate the impact of self-initiated expatriates' perceived person-environment (P-E) fit on their psychological need fulfilment as well as the impact of self-initiated expatriates' perceived psychological need fulfilment on their turnover intentions through the lens of self-determination theory. Utilising an online cross-sectional survey approach, this study tests the proposed hypotheses via the PLS-SEM approach with a sample of 40 self-initiated expatriates in Taiwan. Results illustrate that self-initiated expatriates' person-vocation fit significantly affects their autonomy need fulfilment. Moreover, self-initiated expatriates' person-organisation fit influences their autonomy need fulfilment. Furthermore, self-initiated expatriates' relatedness need fulfilment is predictive of their turnover intention. Limitations and implications are discussed.